DISORIENTASI INKONSTITUSIONAL BERSYARAT DALAM PUTUSAN MAHKAMAH KONSTITUSI - Sutanto, Very Werson (Gapenas Publisher, 2023)
The outlook of Constitutional Court in judging that Omnibus Law is formally disorder while repealing the claim of all claimants by reasoning that there is no legal standing for the claimants to claim is an criteria exceeding as determined by The Acts Numb.24/2004 on Constitutional Court. It brings out disorientation even uncertainty of law itsef. The research aims at analyzing and describing Contitutional Court disorientation of conditional unconstitutional vonnis. Meanwhile, it is also based on conceptual and analytical approach. The idea of conditional-unconstitutional vonnis and conditional-constitutional vonnis came up by inadequacy of vonnis type provided by Chapter 56 The Acts Numb.24/2003 on Constitutional Court. The Court itself must be back to its function